TANGGUNG JAWAB PEMERINTAH DALAM MENJAGA KUALITAS LINGKUNGAN DI WILAYAH PENAMBANGAN INTAN TRADISIONAL CEMPAKA - Abdul Halim Barkatullah; Dadang Abdullah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The word of mining is like two sides of a coin that can not be separated and it always be side by side. In a traditional activity diamond mine in the Cempakaof South Kalimantan is mostly done by individuals, its not only have a positive impact to the surrounding society, especially the impact of economic and welfare society but it has a negative impact too on an environment, especially after mine. The method of the research is used empirical legal research methods. The use of the research method is not merely analyze the law as a series of norms or rules of act associated with the act of vigilantism and the legal process, but need analyze how the law has a positive influence ofthe people's life. Such the legal research, it canbe called as juridical sociological research methods. A traditional mining activity carried out by a group of people or individual needs serious attention, especially in terms of the protection of the environment. Policies regarding mining arenot only the authority of the central government.In this case the autonomous regions have the authority to regulate, so the damage can be prevented as early as possible.Keywords: Traditional Mine, Damage, Environment.